(untitled) (Chemical Engineering Research Bulletin, 2008)
The objective of the study was to treat the textile wastewater and convert it into potable grade water in the laboratory scale. It involved a rigorous treatment procedure involving screening, coagulation, flocculation, aeration, biological treatment, filtration and ion exchange. From the analysis of the treated water it can be saidÂ Â that the industrial waste water can be converted into potable grade water. Keywords: Wastewater treatment, Zero discharge, Potable water. DOI = 10.3329/cerb.v12i0.1493 Chemical Engineering Research Bulletin 12 (2008) 20-23